Improving Transport Costing by using Operation Modeling - Bokor, Zoltán (Transport, 2011)
Transport costing methods applied in practice rely mainly on traditional, accounting approaches. These methods are not able to provide reliable cost of information for decision makers on elementary services as they use arbitrary allocation principles. The operation based on costing is one of the methodological developments whose adaptation can contribute to improve the accuracy of transport cost management. To support costing improvements in transport, this present paper aims to identify the shortcomings of currently used techniques and give a guideline on how to overcome them. The theoretical basics of a new transport costing model are developed while some experiences of early pilot applications are also considered.First Published Online: 07 Jul 2011